2019
DOI: 10.1080/00107514.2019.1586130
|View full text |Cite
|
Sign up to set email alerts
|

Extragalactic background light: inventory of light throughout the cosmic history

Abstract: The Extragalactic Background Light (EBL) stands for the mean surface brightness of the sky as we would see it from a representative vantage point in the intergalactic space outside of our Milky Way Galaxy. Averaged over the whole 4π solid angle it represents the collective light from all luminous matter radiated throughout the cosmic history. Part of the EBL is resolved into galaxies that, with the increasing detecting power of giant telescopes and sensitive detectors, are seen to deeper and deeper limiting ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 157 publications
(211 reference statements)
0
23
0
Order By: Relevance
“…In particular: ESO-VLT (Vernet et al 2009), Pan STARRS (Kaiser et al 2002), Subaru (Taniguchi et al 2007), and CFHT (Capak et al 2007). Nevertheless, the discrepancy between direct and indirect methods is far larger than expected, and the subject of much debate (Mattila & Väisänen 2019). At present the discrepancy in the CIB estimates are ∼ 75%, while in the COB the estimates vary by a factor of 3 to 5.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In particular: ESO-VLT (Vernet et al 2009), Pan STARRS (Kaiser et al 2002), Subaru (Taniguchi et al 2007), and CFHT (Capak et al 2007). Nevertheless, the discrepancy between direct and indirect methods is far larger than expected, and the subject of much debate (Mattila & Väisänen 2019). At present the discrepancy in the CIB estimates are ∼ 75%, while in the COB the estimates vary by a factor of 3 to 5.…”
mentioning
confidence: 85%
“…Unfortunately, despite significant efforts, the current measurements of the COB and CIB exhibit significant inconsistencies most likely associated with the measurement methods (see reviews by Hill et al 2018;Mattila & Väisänen 2019;Driver 2020). Conventionally, these efforts are classified as direct (background sky brightness; Matsumoto et al 2005;Cooray et al 2012;Matsuoka et al 2011;Zemcov et al 2013;Zemcov et al 2017;Kawara et al 2017), and indirect (based on counting galaxies; Madau & Pozzetti 2000;Totani et al 2001;Xu et al 2005;Grazian et al 2009;Keenan et al 2010;Driver et al 2016b).…”
mentioning
confidence: 99%
“…The discrepancy could be as large as factor ∼ (2 − 3) or even more, see e.g. recent review [26]. Our comment here is that the AQNs may fulfill this shortage as the spectrum (2) is very broad and includes optical and IR light.…”
mentioning
confidence: 77%
“…Unfortunately, direct measurements of EBL all-over its wavelength definition range are very difficult, and even largely impossible. Excellent reviews of the subject can be found in [55] for the IR part and in [56] for the optical-UV one. The situation is well illustrated in Figure 1, showing how the Earth is immersed, more than within the EBL photon field, inside a variety of radiations of local origin.…”
Section: Observational Issues Related With the Background Radiationsmentioning
confidence: 99%